2014
DOI: 10.2109/jcersj2.122.772
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Al<sub>3</sub>BC<sub>3</sub> particulates by carbo-thermal reduction process—Parameter optimization and mechanism analysis

Abstract: The synthesis mechanism of Al 3 BC 3 through carbo-thermal reduction process was investigated and the processing conditions were optimized using Al(OH) 3 B 2 O 3 C as starting materials. The mass change and phase formation of the compacts were analyzed with varying temperature. Excess Al(OH) 3 and B 2 O 3 were required compared to the stoichiometric composition due to the loss of the source materials by vaporization at 1,5001,600°C. At 1,600°C, Al 2 O gas began to actively react with carbon to form Al 4 C 3 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Thanks to the strong accelerating effect of the NaCl-NaF binary salt discussed above, essentially phase-pure Al 8 B 4 C 7 particles were successfully prepared at 1250 • C. This synthesis temperature was 350-550 • C lower than that required by the conventional synthesis routes [11,[13][14][15][16][17][18][19][20][21], demonstrating the great advantage and feasibility of the MSS technique developed in this work.…”
Section: Further Discussion and Reaction/synthesis Mechanismsmentioning
confidence: 70%
See 3 more Smart Citations
“…Thanks to the strong accelerating effect of the NaCl-NaF binary salt discussed above, essentially phase-pure Al 8 B 4 C 7 particles were successfully prepared at 1250 • C. This synthesis temperature was 350-550 • C lower than that required by the conventional synthesis routes [11,[13][14][15][16][17][18][19][20][21], demonstrating the great advantage and feasibility of the MSS technique developed in this work.…”
Section: Further Discussion and Reaction/synthesis Mechanismsmentioning
confidence: 70%
“…The particles overall were dispersed well, though some were agglomerated together. The average size of the particles was much smaller, and their dispersion was much better than it was when the conventional synthesis techniques were used [15][16][17][18]. The lattice interlayer spacing (one of the insets in Figure 6) was measured as around 0.29 nm, which corresponds to the (111) plane of hexagonal Al8B4C7.…”
Section: Effect Of Salt Type/assembly On the Formation Of Al8b4c7mentioning
confidence: 98%
See 2 more Smart Citations
“…The average grain sizes of the synthesized (Ti,W)C powders were >100 nm and 10.4–28.3 nm when using the oxide and carbide raw materials, respectively. Lee et al also reported the growth of Al 3 BC 3 particles up to 20 μm when prepared using Al(OH) 3 ‐B 2 O 3 ‐C as the starting materials while the average particle size was 14.1 μm using Al, B 4 C and C as raw materials . Although several reports indicated that the growth of ternary carbides occurred more strongly during synthesis when using the oxide raw materials than carbides, the reasons have not been clearly identified.…”
Section: Resultsmentioning
confidence: 99%